Characterization of the ModABC Molybdate Transport System of Pseudomonas putida in Nicotine Degradation - Xia, Zhenyuan; Lei, Liping; Zhang, Hong-Yue; Wei, Hai-Lei (Frontiers in Microbiology, 2018)
Pseudomonas putida J5 is an efficient nicotine-degrading, bacterial strain that catabolizes nicotine through the pyrrolidine pathway. In our previous study, we used Tn5 transposon mutagenesis to investigate nicotine metabolism-associated genes, and 18 nicotine degradation-deficient mutants were isolated from 16,324 Tn5-transformants. Three of the mutants were Tn5 inserts into the modABC gene cluster that encoded an ABC-type, high-affinity, molybdate transporter. In-frame deletion of the modABC genes abolished the nicotine-degrading ability of strain J5, and complementation with modABC either from P. putida or Arthrobacter oxidans restored the degrading activity of the mutant to the wild-type level. Nicotine degradation of J5 was inhibited markedly by addition of tungstate, a specific antagonist of molybdate. Molybdate at a non-physiologically high concentration (100 μM) fully restored nicotine-degrading activity and recovered growth of the modABC mutant in a nicotine minimal medium. Transcriptional analysis also revealed that the expression of modABC was up-regulated at low molybdate concentrations and down-regulated at high moybdate concentrations, which indicated that at least one other system was able to transport molybdate, but with lower affinity. These results suggested that the molybdate transport system was essential to nicotine metabolism in P. putida J5.